Environmental Loss As An Element Of State Loss In Corruption Offences - Karosekali, Timothy Christian Randal; Frans, Mardian Putra (Fakultas Hukum Dehasen, 2025)
This research aims to discuss legal issues regarding the validity of environmental loss as an element of state loss in criminal acts of corruption. The main aim of this research is to answer the legal issue of whether environmental damage can be categorized as an element of state loss in criminal acts of corruption. The type of research used in this research is normative legal research, namely by examining statutory regulations, legal doctrine, and legal principles related to the problem being studied. The research results show that environmental damage cannot be evidence of a criminal act because Article 2 paragraph (1) and Article 3 of the Corruption Law must be proven by real state financial losses (actual loss) is not a potential or estimated state financial loss (potential loss). Now, law enforcers must be able to prove the real or real value of losses to state finances or the state economy (actual loss), not just based on the potential value of losses that may occur (potential loss)